2013
DOI: 10.1038/npp.2013.306
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia Mediates Methamphetamine-Induced Increases in Glutamate and Excitotoxicity

Abstract: Ammonia has been identified to have a significant role in the long-term damage to dopamine and serotonin terminals produced by methamphetamine (METH), but how ammonia contributes to this damage is unknown. Experiments were conducted to identify whether increases in brain ammonia affect METH-induced increases in glutamate and subsequent excitotoxicity. Increases in striatal glutamate were measured using in vivo microdialysis. To examine the role of ammonia in mediating changes in extracellular glutamate after M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 60 publications
3
46
1
Order By: Relevance
“…Probes for reverse microdialysis were constructed as previously described (Halpin et al, 2014). Briefly, probes were made of PE 20 tubing (Becton Dickinson), silica tubing (OD, 150 μm; Polymicro Technologies), 26 ga stainless steel hypodermic tubing (Small parts), Hollow Fiber Microdialysis Membrane ( active membrane, 1.7 mm; 13,000 molecular cutoff; 216 μm outer diameter; Spectrum Laboratories), 2 ton waterproof epoxy and tygon microbore tubing.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Probes for reverse microdialysis were constructed as previously described (Halpin et al, 2014). Briefly, probes were made of PE 20 tubing (Becton Dickinson), silica tubing (OD, 150 μm; Polymicro Technologies), 26 ga stainless steel hypodermic tubing (Small parts), Hollow Fiber Microdialysis Membrane ( active membrane, 1.7 mm; 13,000 molecular cutoff; 216 μm outer diameter; Spectrum Laboratories), 2 ton waterproof epoxy and tygon microbore tubing.…”
Section: Methodsmentioning
confidence: 99%
“…Surgeries for the probe placement were performed a day before the microdialysis experiment. The microdialysis procedure on next day of probe placement has been shown to provide stable baseline glutamate concentration (Halpin et al, 2014 ). The probes were stereotaxically placed into the NAc (AP+1.8, ML+1.5, DV-6.5/-7mm).…”
Section: Methodsmentioning
confidence: 99%
“…MA also causes alterations in brain structure including gray matter loss, neuronal damage and microgliosis in various regions of the brain [810]. These changes in the brain have been attributed to oxidative stress [11], alteration in blood-brain barrier (BBB) integrity [12], mitochondrial dysfunction [13] and increased excitotoxicity [14]. Recently, the data from our laboratory have also reported increase in proinflammatory cytokines and involvement of cytochrome P450 in MA-mediated oxidative stress as other possible mechanisms for MA-mediated neurotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Recent findings have shown that chronic METH use alters synaptic plasticity in the brain, which may contribute to its adverse effects [35], include dependence, withdrawal syndrome and drug craving [9,17,34]. The METH use causes neurotoxicity in multiple neurotransmitter systems [13,18,41]. METH-induced alterations in dopamine levels in mesolimbic, nigrostriatal systems and prefrontal cortex involve in craving and rewarding effects of drug [16,28].…”
Section: Introductionmentioning
confidence: 99%